The Atlantic thermohaline circulation in extreme climates - Lecci, Rita (Università Ca' Foscari Venezia, 2012)
The present study investigates the sensitivity of the Atlantic Thermohaline Circulation (ATHC) to extreme external radiative forcing with the aim to contribute to the understanding of the mechanisms at work. A set of long experiments performed with a state of the art atmosphere-ocean coupled general circulation model under strong atmospheric CO2 forcing has been used to study the mechanisms controlling the ATHC changes, their effects in the North Atlantic climate and in the energetics of the climate system. The ATHC weakens in response to a warming of atmosphere and ocean affecting the northward heat transport and leading to its decrease into the basin. The most extreme case shows distinctive features with an equatorward shift of ATHC convective sites and a salinity front formation at midlatitudes. The analysis of the mechanisms at work shows a positive relationship between the high latitudes ocean vertical diffusivity and the circulation intensity. The Southern Ocean wind stress seems to influence the ATHC only when the meridional density gradients between high and low latitudes in the basin are kept fixed with a weaker Southern Ocean wind stress leading to a weaker ATHC. The meridional density gradients between high and low latitudes have been found inversely related to the ATHC intensity in the CO2 simulations with the exception of the most extreme case. The high-density Mediterranean Outflow waters influence the ATHC as well: the ocean circulation decreases and shifts to mid-latitudes in response to a salinity input at the Gibraltar Strait latitude. The weakening of the ATHC under increasing C02 atmospheric concentration has been found associated with a large decrease of the kinetic energy input, mainly by the pressure-gradient work in the convective site areas in the North Atlantic. On the other hand, the atmospheric kinetic energy increases because of the intensification and poleward shift of the mid-latitudes jet-streams, the troposphere tends to be more stable and the Hadlev circulation weakens.